2022
DOI: 10.1161/circresaha.121.319044
|View full text |Cite|
|
Sign up to set email alerts
|

Activated Protein C Strengthens Cardiac Tolerance to Ischemic Insults in Aging

Abstract: Background: Activated protein C (APC) is a plasma serine protease with anticoagulant and anti-inflammatory activities. Endothelial protein C receptor (EPCR) is associated with APC's activity and mediates its downstream signaling events. APC exerts cardioprotective effects during ischemia and reperfusion (I/R). This study aims to characterize the role of the APC-EPCR axis in ischemic insults in aging. Methods: Young (3-4 months) and aged (24-26 months) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Restore blood supply in time to ischemic myocardium is the most effective treatment for AMI. Reperfusion is a viable therapeutic strategy for ischemic heart disease with high morbidity and mortality ( Ren et al, 2021 ). However, reperfusion may also exacerbate myocardial damage and produce a second blow to the myocardium, such as excessively generating reactive oxygen and nitrogen species ( Daiber et al, 2021 ), increasing release of inflammatory mediators and recruitment of inflammatory cells ( Toldo et al, 2018 ), mitochondrial Ca 2+ overload, and the opening of the mitochondrial permeability transition pore (MPTP) ( Ong et al, 2015 ; Basalay et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Restore blood supply in time to ischemic myocardium is the most effective treatment for AMI. Reperfusion is a viable therapeutic strategy for ischemic heart disease with high morbidity and mortality ( Ren et al, 2021 ). However, reperfusion may also exacerbate myocardial damage and produce a second blow to the myocardium, such as excessively generating reactive oxygen and nitrogen species ( Daiber et al, 2021 ), increasing release of inflammatory mediators and recruitment of inflammatory cells ( Toldo et al, 2018 ), mitochondrial Ca 2+ overload, and the opening of the mitochondrial permeability transition pore (MPTP) ( Ong et al, 2015 ; Basalay et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, given the observed protective effects of cytoprotective APC variants, such as 3K3A-APC, in other pathologies this warrants further investigation. 20 , 42 , 43 , 44 …”
Section: Discussionmentioning
confidence: 99%
“…Many obese patients have been shown to develop fibrosis of the myocardium [ 27 , 29 ]. Further, these fibrotic changes have been found to be connected to ventricular stiffness and diastolic dysfunction [ 29 , 30 , 32 ]. Here, we observed that obese mice and humans experienced greater amounts of fibrosis in tissue of the left ventricle compared to their counterparts that were of a more ideal weight or BMI.…”
Section: Discussionmentioning
confidence: 99%